A Multi-Rater Study on Being Teased Among Children/Adolescents With Autism Spectrum Disorder (ASD) and Their Typically Developing Siblings: Associations With ASD Symptoms. (December 2014) - Nowell, Kerri P.; Brewton, Christie M.; Goin-Kochel, Robin P.
The study examined teasing experiences among 74 individuals with autism spectrum disorder (ASD; M age = 115.7 months [9.6 years]; 83.8% male). Experiences were examined from parent, teacher, and child's own perspectives. Factors potentially associated with being teased were investigated. Comparison data were ascertained on typically developing siblings ( n = 68; M age = 116.5 months [9.7 years]; 52.9% male). Select items on the Child Behavior Checklist 6–18 and the Teacher Report Form 6–18 were utilized to calculate the prevalence of being teased; qualitative data from a subgroup of verbally fluent children with ASD ( n = 50) were analyzed to provide child self-report teasing data. Children with ASD were more likely to be teased than their typically developing siblings. Characteristics that were significantly associated with being teased included higher cognitive functioning, less severe ASD symptomatology, and more time spent in inclusive educational settings. Clinical implications are discussed.